Navigating the Corporate Interview Negotiation: Strategies and Insights - Zhang, Junsheng (Transactions on Economics, Business and Management Research, 2024)
This study investigates the critical role of effective negotiation in job interviews and presents tactics to refine interviewees' negotiation capabilities. The research underscores that negotiation extends beyond obtaining a job position; it is instrumental in molding one's professional trajectory and financial destiny. The paper advocates for comprehensive preparation, encompassing insights into industry norms and corporate financial, to bolster interviewees' negotiation leverage. It also accentuates psychological tactics, such as the anchoring effect and demonstrating passion, as pivotal in swaying negotiation results. Additionally, the paper discusses the value of considering non-salary benefits, including health insurance and retirement plans, in the negotiation process. Candidates are recommended to scrutinize employment contracts and seek legal counsel when required. Furthermore, the study emphasizes the importance of practicing active listening and empathy to build rapport with interviewers, which can further enhance the negotiation process. Ultimately, the paper concludes that proficiency in negotiation can markedly enhance job seekers' prospects of achieving improved employment terms and career progression.